Study on the health risk of cyanuric acid in swimming pool water and its prevention and control measures - Chen, Zhe; Su, Yi; Chen, Jian; Li, Zhu; Wang, Ting (Frontiers in Public Health, 2024)
Cyanuric acid is a widely used fine chemical intermediate that acts as a free chlorine buffer in swimming pool water, wherein it is often used as a stabilizer to maintain the germicidal efficacy of chlorinated disinfectants. However, it has also been associated with health risks. Herein, we introduced the sources and functions of cyanuric acid in swimming pool water, focusing on potential health risks associated with excessive concentration of the component and the current control standards worldwide. Also, the prevention and control measures were summarized in terms of physical chemistry, biodegradation, and ultraviolet radiation to provide a basis for the development of public health policies for swimming pool management.